Marketing sports coaching services : assessing trust on social network sites and its relation to purchase intention - Koh, Jia Yi (2017)
Coaching has been recognized as a key aspect in improving sports performance alongside the growth of Singapore’s sports industry. Yet, engaging sports coaches has not been a common practice here. Limited research has been done on marketing sports coaching services, especially on increasingly popular platforms such as social network sites (SNS). For consumers, decisions to purchase services with intangible output, such as coaching, has been found to be influenced by sources of credibility, such as trust. Concurrently, levels of trust has been found to vary across different age demographics. The purpose of this study is to investigate marketing of sports coaching on SNS to different demographical age groups and a further analysis of the trust and purchase intention (PI) is considered between them. An online questionnaire focusing on the level of trust and PI on Facebook were conducted on 269 respondents who plays badminton once a month, categorized them between 3 different age groups (18-25), (26-40) and (41-60). The results suggested that trust and PI on SNS had a significant result between ages 18-40 when compared to ages 41-60 individually, additionally, trust and PI had a strong correlation. Sport marketers may utilize the findings of this study to formulate appropriate marketing strategies, leveraging on established SNS that consumers trust (e.g. Facebook) and encourage higher purchasing intention between consumers aged 18-40. Future studies could include considering other variables such as differences in gender and different websites to explain how they might influence trust and purchase intention on SNS.